Ecology at the Heart of Faith - Edwards, Denis (Orbis Books, 2006)
Beginning with the words, "One of the gifts we have received from the twentieth century is a picture of Earth as our shared home," Denis Edwards helps the general reader, the preacher, the spiritual director, the student and the theologian tear down the walls that too often separate mysticism, theology, prophecy, poetry, and science. In a world born of the "big bang," Edwards shows that humanity and the world are together being made into the image of God. The heart of faith is an ecological communion holds together and grows in love toward the fullness of life imaged in the Resurrection of Jesus.